Spectrum sensing algorithm based on symmetry of cyclic spectral correlation - Yu-long GAO; Yan-ping CHEN; Xiu-zhi GUAN; Zhong-zhao ZHANG; Xue-jun SHA (Tongxin xuebao)
In response to the shortcoming of conventional algorithms,modified SSCA was exploited to calculate the cyclic spectral correlation of received signal for decreasing the computational complexity.Symmetry of cyclic spectral correlation (CSC) was used to detect the idle spectrum,criteria and method of selecting and judging symmetry were proposed.Conventional binary hypothesis condition was translated to concrete value according to symmetry.In order to eliminate the effect of interference and noise,non-zero cyclic frequencies were selected.Finally,the performance of the presented algorithm was compared with the conventional algorithms by virtue of simulation.Simulation results proved the correctness and the superiority of new algorithms.Using symmetry improves the successful detection probability for low SNR and reduces the computational complexity.